2002
DOI: 10.1016/s0002-9440(10)64357-x
|View full text |Cite
|
Sign up to set email alerts
|

Podocin Localizes in the Kidney to the Slit Diaphragm Area

Abstract: We recently cloned a novel gene, NPHS2, involved in autosomal recessive steroid-resistant nephrotic syndrome. This gene encodes a novel podocyte protein, podocin. Given its similarity with the stomatin family proteins, podocin is predicted to be an integral membrane protein with a single membrane domain forming a hairpin-like structure placing both N- and C-termini in the cytosol. Here, we show by in situ hybridization, that during development, the NPHS2 transcript is first expressed in mesonephric podocytes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
219
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(238 citation statements)
references
References 25 publications
15
219
0
4
Order By: Relevance
“…For a long time the glomerular basement membrane (GBM) has been considered to be the main barrier for filtration. More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…For a long time the glomerular basement membrane (GBM) has been considered to be the main barrier for filtration. More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 73%
“…Under normal conditions, the glomerular barrier restricts the passage of macromolecules such as albumin, while it is highly permeable to water and small solutes. The underlying mechanisms leading to proteinuria are still poorly understood, although the importance of the podocyte for glomerular integrity has been clearly documented [1][2][3]. Consequently, there is no specific therapy for diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…While their SPFH domains are predicted to be globular, the C termini seem more likely to be unfolded and lack multiple EA motifs. Finally, podocin is an integral membrane protein exclusively expressed in podocytes of the kidney, and plays a key role in the stability of glomerular slit diaphragm [45]. Podocin contains an SPFH domain covering about 40% of the polypeptide (human position 123-279) and a transmembrane domain (positions 102-128).…”
Section: Resultsmentioning
confidence: 99%
“…Stomatin is present as high-order oligomers in erythrocyte lipid rafts, where it has a scaffolding function (83). Podocin localizes to the SD (16,21), accumulates there in an oligomeric form in lipid rafts and associates via its C-terminus with CD2AP and nephrin (16). Further studies revealed direct interaction of podocin and CD2AP (16).…”
Section: Podocin Interacts With Cd2ap and Nephrinmentioning
confidence: 98%
“…Neighboring FP are connected by a cell-cell junction, the glomerular SD, which represents the main size selective filter barrier in the kidney (8 -10). The SD is thought to be a modified adherens junction (11) that is composed of a growing number of proteins, including nephrin (12)(13)(14), P-cadherin, CD2AP (15)(16)(17)(18), ZO-1 (19), FAT (20), podocin (16,21), and possibly Neph1 (see reference 22 and below). In addition to the contractile proteins described above, we have reported the association of synaptopodin with the actin filaments in FP (23).…”
Section: Molecular Anatomy Of the Podocyte Fp Cytoskeletonmentioning
confidence: 99%